CHELATING ABILITY OF CRAB SHELL PARTICLES AND EXTRACTED ACETAMIDO GROUPS (CHITIN AND CHITOSAN) FROM Portunus sp TO LEAD (Pb2+) - Moh Muhaemin (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Various toxic metal species, including lead, are produced rapidly by industrial activities and fossil fuelconsumption. The use of biological component as sorbents for heavy metals might be an alternativemethod to reduce a heavy metal concentration from various aqueous systems. Here, we used crab shellparticles and extracted acetamido component from Portunus sp (chitin and chitosan) to reduce theconcentration of lead (II). The crab shell was powdered, sieved, and added with lead (II) in various pHvalues. The lead (II) solution added to extract of chitin and chitosan was separated, to determine thechelating ability of them. The result showed that the removal efficiency of lead with crab shell depend onpH value, but it was less sensitive than that of the control without crab shell. Biosorption of chitin andchitosan showed different phenomenon. It showed that both chitin and chitosan absorb with the bestcapacity at pH 4.0. Chitosan has higher sorption than chitin for all treatments.